Analisis Hukum Terhadap Putusan Pengadilan Mengenai Gugatan Ditolak karena Itikad Tidak Baik dalam Mediasi - Kameria, Cica; Ahmad, Akiruddin; Sahbudi, Sahbudi (Universitas Medan Area, 2025)
The background to this research is a court ruling rejecting a lawsuit because the plaintiff failed to demonstrate good faith during the mediation process, even though, in principle, everyone has the right to file a lawsuit. The purpose of this research is to determine the legal basis for the court's decision to reject the lawsuit due to a lack of good faith during the mediation process and to analyze its legal implications for the parties. The research method used is normative legal research with a statute approach and a conceptual approach. The research data sources were obtained from primary, secondary, and tertiary legal materials and analyzed qualitatively. The results indicate that the legal basis for rejecting the lawsuit due to a lack of good faith during the mediation process refers to Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court. This ruling has legal implications, namely, that the lawsuit is declared inadmissible (niet ontvankelijk verklaard), resulting in the plaintiff having to file a new lawsuit, obligated to diligently follow the mediation process.z